Unpacking the Pain: Understanding Barriers and Unmet Needs of Adults with Low Back Pain in a Southern Nigeria Outpatient Clinic - Muoghallu, Obianuju Iheomamere; Mark, Akaninyene; Akafa, Tensaba Andes; Oladele, Gloria Omonefe; Iseko, Kingsley Iyoko (Darul Yasin Al Sys, 2025)
Background: Low back pain (LBP) is a prevalent health issue leading to functional disability in adults. This study aimed to evaluate the barriers to care and unmet needs of adults with LBP and functional disability attending the General Out-Patient Clinic (GOPC) at the University of Uyo Teaching Hospital, Akwa Ibom State. The goal is to enhance quality of life by reducing disability and LBP burden through prevention, addressing barriers, and fulfilling unmet needs. Key barriers identified include limited access to healthcare, high out-of-pocket costs, inadequate insurance coverage, and a lack of understanding of LBP and self-management strategies. Methodology: Conducted at the GOPC, this cross-sectional analytical study involved 370 adult patients (18+ years) using systematic sampling. Data collection spanned two months, employing an interviewer-administered semi-structured Oswestry lumbar disability questionnaire. Analysis utilized IBM SPSS version 27, with frequency tables for pain patterns and chi-square tests to assess associations between body mass index (BMI) and LBP severity. Results: The mean age of respondents was 40.2 years. LBP was significantly linked to low function, with the association strengthening over time. Most respondents were classified as obese (BMI 25.0-29.9 kg/m²), and 56.7% reported high pain intensity. Activities like lifting weights and sitting exacerbated pain for 70.3% and 66.2% of respondents, respectively. The median pain score was 52, with significant differences noted (p<0.001). Alcohol consumption was reported by 39.6% (p=0.005), while 72.2% did not smoke. Respondents with LBP were 1.70 times more likely to experience functional disability compared to those without. Conclusion: LBP is strongly associated with functional disability among adults. Unmet needs include limited rehabilitation access, inadequate education on LBP, and insufficient support for self-management. Addressing risk factors, implementing multi-modal pain management strategies, and enhancing health education are essential for preventing functional disability.